Acute Moderate Intensity Exercise Decreases Oxygen Saturation In Obese Women - Coli, Cornelius; Sari, Gadis Meinar; Rejeki, Purwo Sri (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study aims to analyze acute moderate intensity exercise decreases oxygen saturation in obese women. True experiment with a randomized control group design posttest-only design using 14 obese women aged 19-24 years, body mass index 27-33 kg/m2, percentage body fat (PBF) above 30 % and fasting blood glucose (FBG) below 100 mg/dL, normal hemoglobin, normal systolic and diastolic blood pressure, normal resting heart rate and randomly divided into two groups, namely CON (n=7, control without intervention) and MIE (n=7, moderate intensity exercise). Moderate intensity exercise interventions carried out for 40 minutes using a treadmill. Blood sampling is done 10 minutes after the intervention. Measurement of oxygen saturation using a Pulse Oximeter. The results obtained mean oxygen saturation at CON (98.428±0.534) % and MIE (96.571±0.975) % (p=0.001). Based on the results of the study concluded that moderate moderate intensity acute exercise reduces oxygen saturation in obese women.